Removal Of Synthetic Methyl Orange DYE At Neutral pH BY NR-b-PVP/Ag Using Photodegradation Technique - Md Razif, Muhammad Faiz Syazwan (Universiti Sains Malaysia, 2018)
Effluent of wastewater from textile industries need to be treated before discharge into environment as this wastewater contains high toxicity which can lead to serious water pollution. Environmentally friendly, low cost dye wastewater treatment model have been produced in order to solve this issue. NR-b-PVP/Ag film prepared from blends of natural rubber latex with polyvinylpyrrolidone incorporated with silver particle was coated onto the surface of the glass to degrade methyl orange (MO) dye via photodegradation at neutral pH. The process of photodegradation was conducted under the sunlight for 2 hours and 2 mL of sample was taken to analyse the absorbance capacity at peak wavelength of MO, 463 nm, via UV-Vis Spectrophotometer for every 20 minutes. This thesis emphasizes the effect of method setup of the glass, effect of silver nitrate (AgNO3) concentration and effect of flowrate of the MO solution. The highest degradation of 5 Liters of MO solution achieved in this study was 86.6% when Glass Combine method, 0.3 g/mol of AgNO3 with 400 mL/min was applied.